High Serum High Mobility Group A1 (HMGA1) Levels are associated with Presence of Metabolic Syndrome: Case-Control Study - Faiq, Mirna K.; Saleh, Eman S.; Fathalla, Omar B. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Metabolic syndrome is a complex series of metabolic defects characterized by high levels of serum glucose, hypertension, abdominal obesity, and dyslipidemia. The high mobility group AT-hook1, an architectural transcript factor, affects the homeostasis of glucose. No previous studies have been performed to examine whether HMGA1 can be secreted into the extracellular milieu. Objectives: This case-control study aimed to examine whether HMGA1 secretes into the extracellular milieu and compare its serum level in two groups of metabolic syndromes (with and without diabetes) and a control group composed of apparently healthy individuals of the Iraqi population with different nationalities. Methods: Sixty-one patients with metabolic syndrome and thirty healthy Iraqi participants were included in this study. Serum HMGA1 concentrations were determined by enzyme-linked immunosorbent assay (ELISA). Lipid profile, serum (glucose and insulin), HbA1c, systolic/diastolic blood pressure, body mass index, and waist circumference were also measured. The statistical analysis was done using IBM SPSS software for Windows version 26.0. Results: A significant difference in HMGA1 level was seen (P = 0.000) between metabolic syndrome with diabetes, metabolic syndrome without diabetes, and the control group. Higher concentrations were seen in metabolic syndrome patients with diabetes, followed by metabolic syndrome patients without diabetes and then the control group, and no significant difference was seen in the serum level based on nationality. A significant positive correlation was found between HMGA1 and fasting blood glucose (p = 0.001) as well as between HMGA1 and HbA1c (p= 0.015) in patients with metabolic syndrome. Moreover, there was a significant association between HMGA1 levels and the risk of metabolic syndrome. The risk of metabolic syndrome was found to be increased by a high HMGA1 level, odds ratio (OR), 0.411 (95% CI, 0.208-0.813). Conclusions: This case-control study found that circulating HMGA1 concentration was significantly higher in Mets, mainly in those with T2DM. Also, the high concentration of HMGA1 was found to present a significant risk of metabolic syndrome regardless of whether diabetes is present or not. Besides HMGA1 serum level was positively correlated with parameters of diabetes including HbA1c and FBG.